Race pattern of 60-m hurdles in world-class sprint hurdlers: a biomechanical analysis of world indoor championships 2010 - Poon, S.; Kuitunen, S. (ISBS - Conference Proceedings Archive (Konstanz), 2010)
Earlier competition reports of sprint hurdle performances show that the world-class hurdle sprinters achieve their maximal race velocity somewhere between the third and sixth hurdle (Brüggemann & Glad, 1990; Brüggemann et al., 1999). No competition analysis has been done for the indoor sprint hurdle performance, where the official distance is 60 meters consisting of five hurdles. It is not known if the hurdle sprinters change their race pattern towards a more aggressive start in the 60-m hurdle race. The purpose of the present study, therefore, was to examine the race pattern of 60-m hurdles in world-class sprint hurdlers.